Total parasite biomass but not peripheral parasitaemia is associated with endothelial and haematological perturbations in Plasmodium vivax patients - João L Silva-Filho; João CK Dos-Santos; Carla Judice; Dario Beraldi; Kannan Venugopal; Diogenes Lima; Helder I Nakaya; Erich V De Paula; Stefanie CP Lopes; Marcus VG Lacerda; Matthias Marti; Fabio TM Costa (eLife, 2021)
Plasmodium vivax is the major cause of human malaria in the Americas. How P. vivax infection can lead to poor clinical outcomes, despite low peripheral parasitaemia, remains a matter of intense debate. Estimation of total P. vivax biomass based on circulating markers indicates existence of a predominant parasite population outside of circulation. In this study, we investigate associations between both peripheral and total parasite biomass and host response in vivax malaria. We analysed parasite and host signatures in a cohort of uncomplicated vivax malaria patients from Manaus, Brazil, combining clinical and parasite parameters, multiplexed analysis of host responses, and ex vivo assays. Patterns of clinical features, parasite burden, and host signatures measured in plasma across the patient cohort were highly heterogenous. Further data deconvolution revealed two patient clusters, here termed Vivaxlow and Vivaxhigh. These patient subgroups were defined based on differences in total parasite biomass but not peripheral parasitaemia. Overall Vivaxlow patients clustered with healthy donors and Vivaxhigh patients showed more profound alterations in haematological parameters, endothelial cell (EC) activation, and glycocalyx breakdown and levels of cytokines regulating different haematopoiesis pathways compared to Vivaxlow. Vivaxhigh patients presented more severe thrombocytopenia and lymphopenia, along with enrichment of neutrophils in the peripheral blood and increased neutrophil-to-lymphocyte ratio (NLCR). When patients’ signatures were combined, high association of total parasite biomass with a subset of markers of EC activation, thrombocytopenia, and lymphopenia severity was observed. Finally, machine learning models defined a combination of host parameters measured in the circulation that could predict the extent of parasite infection outside of circulation. Altogether, our data show that total parasite biomass is a better predictor of perturbations in host homeostasis in P. vivax patients than peripheral parasitaemia. This supports the emerging paradigm of a P. vivax tissue reservoir, particularly in the haematopoietic niche of bone marrow and spleen.